Economic Policy Uncertainty and Equity Fund Flows to India: A Bayesian Approach - Martin, Michael; McClatchey, Christine; French, Joseph J. (The Indian Economic Journal, 2024)
We compare the impacts of economic policy uncertainty (EPU) and global economic policy uncertainty (GEPU)-related shocks on equity fund flows (EFFs) to India using a Bayesian vector autoregression approach. We find that (a) Indian EPU and GEPU are strongly and negatively related to EFF; (b) EFF are more sensitive to GEPU relative to Indian EPU; (c) evidence of trend-chasing behaviour by fund managers in India; and (d) GEPU is an important factor for forecasting returns on the Bombay Stock Exchange. Taken together, our findings indicate that EPU is important to understanding equity allocation decisions and returns in India.JEL Codes: F21, F39, G11
Keywords: Bombay Stock Exchange; Global Economic Policy; Economic Policy